Housing Choices as School Choices: Subsidized Renters' Agency in an Uncertain Policy Context. (December 2016) - Bender, Annah; Metzger, Molly; Murugan, Vithya; Ravindranath, Divya
Previous scholarship on the federal Housing Choice Voucher (HCV) program has found that HCV renters are less likely than other households living below the poverty line to live in neighborhoods with high–performing schools. These findings are troubling because HCV renters have some choice about where they live, yet aggregate data linking HCV renters' neighborhoods with school performance shows that renters tend to be concentrated in impoverished areas with poor schools. To better understand whether and how schools factor into HCV renters' neighborhood preferences when searching for a home, semistructured interviews with 17 HCV heads–of–household in the St. Louis region were conducted. Findings from this project reveal that some HCV renters prioritize school choice when deciding to move, sending their children to schools that may or may not be located within their neighborhood. A minority of families in this study actually enrolled their children in the school district indicated by their address. Three families had intentionally moved to unaccredited districts to take advantage of a transfer law that allowed students in unaccredited school districts to attend an out–of–district school. Although not a direct counterpoint to previous scholarship, these findings lend some balance to the idea that HCV renters are compelled to live in districts with lower property values and thus lower performing schools than other households receiving government assistance. HCV renters encounter many constraints on their choice of housing and neighborhood, and legacies of racism, housing discrimination, and predatory landlords may indeed limit renters to poor neighborhoods with underperforming school districts, but as interviews with 17 participants with school–age children demonstrate, their children may not be attending their neighborhood schools after all. These findings help contextualize HCV renter concentration in low–income neighborhoods, while further research is needed to address the education and housing policy ramifications of this work on a national scale.